2011
DOI: 10.1542/peds.2010-3017
|View full text |Cite
|
Sign up to set email alerts
|

Receipt of Health Care Transition Counseling in the National Survey of Adult Transition and Health

Abstract: Many young adults reported not having received health care transition counseling. Provider-youth communication was associated with increased health care transition guidance, and suggests that a medical home model that promotes anticipatory guidance for health care transition could promote improvements in the transition process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 18 publications
3
34
1
Order By: Relevance
“…Similar indicators have been shown to predict receipt of HCT services in YSHCN and in the general young adult population. 17,18,26 Although target population and severity measurements varied considerably, these studies reported similar findings; ie, as the complexity of condition increases, the likelihood of receiving HCT services decreases. The comorbid condition variables used within the present study may be a more accurate measure of complexity because it is not as subjective as parental report of functioning and activity limits.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Similar indicators have been shown to predict receipt of HCT services in YSHCN and in the general young adult population. 17,18,26 Although target population and severity measurements varied considerably, these studies reported similar findings; ie, as the complexity of condition increases, the likelihood of receiving HCT services decreases. The comorbid condition variables used within the present study may be a more accurate measure of complexity because it is not as subjective as parental report of functioning and activity limits.…”
Section: Discussionmentioning
confidence: 70%
“…17,18,21,26 Individual demographic explanatory variables included age, gender, and race/ethnicity (Table 1). Youth' s mental and physical health was examined by using several variables related to severity of health conditions and presence of comorbid conditions.…”
Section: Explanatory Variablesmentioning
confidence: 99%
“…[353][354][355] Early development of staged and timely transition processes and programs geared toward education, and modifiable for individualized patient diagnosis and complicit concerns, is greatly needed. [356][357][358][359][360] It is recommended that education through accurate dissemination of information begin at an early stage in the patient healthcare process and directly involve caregivers, providers, support staff, and the patient. 351,[361][362][363] Patients with NMDs are likely to benefit from a coordinator-directed, multidisciplinary team approach, which can provide important support in negotiating communication gaps between providers and enable a systematic clinical transition and education process on health, adult care providers, facilities, and financial and medical resources.…”
Section: Transition Of Carementioning
confidence: 99%
“…351,[361][362][363] Patients with NMDs are likely to benefit from a coordinator-directed, multidisciplinary team approach, which can provide important support in negotiating communication gaps between providers and enable a systematic clinical transition and education process on health, adult care providers, facilities, and financial and medical resources. 351,353,358,364,365 …”
Section: Transition Of Carementioning
confidence: 99%
“…22 Furthermore, among young adults aged 19 to 23 with SHCN who had transitioned to adult care, although 50% reported having received advice from their pediatric providers regarding how their needs would change with age, how to obtain health insurance, or how to participate in a transition plan in school, only 24% received counseling in all 3 areas. 23 In 2011 the American Academy of Pediatrics published a clinical report that promotes a developmental model for HCT preparation within the context of the medical home. 24 The report recommends that providers regularly and objectively assess patients' disease self-management and health care utilization skills.…”
mentioning
confidence: 99%